Do Funding Conditions Explain the Relation Between Cash Holdings and Stock Returns? - Jensen, Tyler K. (Journal of Financial and Quantitative Analysis, 2022)
Abstract The prior literature links cash holdings and returns (Simutin (2010), Palazzo (2012)). Using two signals of aggregate-funding availability, I find that the positive association between cash and returns only exists during constrained funding environments. In unconstrained periods, there is no association between cash and returns. The relation in constrained environments does not appear to be related to capital expenditures, expected return, or distress risk but is more prevalent in firms undertaking research and development (R&D) expenditures. This suggests that the association between cash and returns is more consistent with expanding (or maintaining) future growth opportunities rather than being attributable to differences in capital expenditures or risk.